2021
DOI: 10.3389/fneur.2021.746468
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Lobe Spikes Affect Distant Intrinsic Connectivity Networks

Abstract: Objective: To evaluate local and distant blood oxygen level dependent (BOLD) signal changes related to interictal epileptiform discharges (IED) in drug-resistant temporal lobe epilepsy (TLE).Methods: Thirty-three TLE patients undergoing EEG–functional Magnetic Resonance Imaging (fMRI) as part of the presurgical workup were consecutively enrolled. First, a single-subject spike-related analysis was performed: (a) to verify the BOLD concordance with the presumed Epileptogenic Zone (EZ); and (b) to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…Interictal epileptiform discharges (IEDs) may interrupt the usual local and remote neuronal propagation (Mirandola et al, 2021), although decreased connectivity in the EZ has been described in the absence of interictal spikes (Coito et al, 2016). In contrast, abnormal connections arising from epileptic networks occur in the absence of interictal spikes and are reinforced by their presence (Iannotti et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Interictal epileptiform discharges (IEDs) may interrupt the usual local and remote neuronal propagation (Mirandola et al, 2021), although decreased connectivity in the EZ has been described in the absence of interictal spikes (Coito et al, 2016). In contrast, abnormal connections arising from epileptic networks occur in the absence of interictal spikes and are reinforced by their presence (Iannotti et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Su ubicación anatómica estratégica permite que sea una vía común para la propagación de descargas epileptiformes en las epilepsias focales. Esto se correlaciona con algunos estudios de neuroimagen los cuales han demostrado que, en pacientes con epilepsia del lóbulo temporal, la disfunción de los circuitos anatómicos va más allá del hipocampo y afecta a muchas otras estructuras (24)(25)(26). Estos estudios han identificado cambios volumétricos y morfológicos en la CPR, lo que sugiere que su atrofia es ipsilateral al foco epiléptico.…”
Section: Implicaciones De La Corteza Piriforme En La Epileptogénesis ...unclassified
“…One study reported the accuracy of EEG‐fMRI in localizing the seizure‐onset zone (SOZ) with stereo‐EEG (SEEG) and found that 77% of patients had at least one study with primary EEG‐fMRI clusters concordant with an SEEG‐defined SOZ 15 . Another study claimed that the spike‐related BOLD response represented intrinsic connectivity networks 16 . Several studies have proposed routine clinical use of EEG‐fMRI in the pre‐surgical evaluation of medically refractory epilepsy patients 17–21 .…”
Section: Introductionmentioning
confidence: 99%
“… 15 Another study claimed that the spike‐related BOLD response represented intrinsic connectivity networks. 16 Several studies have proposed routine clinical use of EEG‐fMRI in the pre‐surgical evaluation of medically refractory epilepsy patients. 17 , 18 , 19 , 20 , 21 However, these reports did not assess the added value of EEG‐fMRI in a standard clinical evaluation.…”
Section: Introductionmentioning
confidence: 99%